PELATIHAN PEMASARAN PRODUK PERTANIAN (PACKAGING, BRANDING, PROMOTING DAN DIGITAL MARKETING) SEBAGAI BENTUK WIRAUSAHA SEJAK DINI BAGI SISWA - Yulia Yulia; Juma Riah; Desti Asfina (ASOSIASI IDEBAHASA KEPRI, 2026)
Digital marketing is a marketing strategy that uses digital platforms and the internet (such as social media, search engines, and websites) to promote products or services. Micro-businesses in Batam upload photos or videos of their products to social media and provide engaging content to attract consumers. The Yaa Bunayya Orphanage in Batam has housed many orphaned and abandoned children, with a total of 53 foster children, 33 of whom are high school/vocational school students. To support its operational activities, the orphanage is open to donations and community contributions. Agricultural products such as corn, bananas, sweet potatoes, and others are also a source of income for the orphanage. The problem that occurred at the Yaa Bunayya Orphanage was that agricultural products were sold to traditional markets at low prices. The result of this community service is that students are able to understand product marketing using digital marketing, starting from the packaging, branding, promotion, and digital marketing stages for high school/vocational school students at the Yaa Bunayya Orphanage in Batam. Introduction to and utilization of digital marketing in the form of online media in marketing, including social networking, blogs, media sharing, social bookmarking, wikis, and others. Understanding marketing as a form of entrepreneurship from an early age.